An audit of antibiotic prescribing in primary care 2019-2020 in Dunmanway Primary Care Centre - Kate Ryan; Tom O'Donnell; Ann Kiely; Deirdre Scully; Mary Wickham; Allan Harris; Michelle Ryan (James Cook University, 2023)
Introduction: Antibiotics are often the most common medication prescribed by general practitioners (GPs) and are often expected by patients despite campaigns such as Under the Weather. Antibiotic resistance is increasing in the community. The Health Service Executive (HSE) has issued ‘Guidelines for Antimicrobial Prescribing in Primary Care in Ireland’ aiming to optimise safe prescribing. This audit aims to analyse change in quality of prescribing after educational intervention.Methods: GP prescribing patterns were analysed over a week in October 2019 and re-audited in February 2020. Anonymous questionnaires detailed demographics, condition and antibiotic details. Educational intervention included texts, information and review of current guidelines. Data were analysed on a password protected spreadsheet. The HSE Guidelines for Antimicrobial Prescribing in Primary Care were taken as reference standard. A standard of 90% compliance for choice of antibiotic and 70% compliance for dose and course was agreed.Results:FindingsAuditRe-AuditNumber prescriptions4024Number delayed scripts4/40=10%1/24=4.2%Adult37/40=92.5%19/24=79.2%Child3/40=7.5%5/24=20.8%IndicationURTI22.50%25%LRTI10%4%Other RTI37.50%42%UTI20%29%Skin12.50%0%Gynaecological2.50%0%2+ Infections 5%0%Co-amoxiclav17.50%12.50%AdherenceChoice37/40=92.5%22/24=91.7%Dose28/39=71.8%17/24=70.8%Course28/40=70%12/24=50%Discussion: Excellent antibiotic choice and dose concordance with guidelines was noted, with both phases meeting the set standards. Suboptimal course compliance with guidelines occurred in the re-audit. Potential causes include concerns regarding resistance and patient factors not included. This audit included unequal number of prescriptions in each phase but are still of significance and addresses a clinically relevant topic.